The Supernatural after the Neuro-Turn (Milton)
1 online resource (189 p.)
Keywords: This book takes what is often referred to as the "supernatural" to be normal natural phenomena that are closely linked to the neurobiology of the human species. Reflecting the neurocultural and biocultural perspective, the chapters cover phenomena such as out-of-body experiences, ghosts, and experiences of spirit entities. The contributors consider the "supernatural" as emerging from innate neurobiological structures and functions, and reflecting known neurobiological processes that explain their universality and persistence.